"The difference of colour": reading and writing abolitionism. (2nd January 2019) - Kelley, Mary
ABSTRACT: Through an analysis of words and images as they moved through material production, circulation, and reception, "The Difference of Colour" explores the literary and pictorial practices of African American women who read and wrote antislavery. Calling on antebellum Americans to join them in the struggle against slavery and racial prejudice, the women who formed Philadelphia's Female Literary Association articulated a powerful antislavery at a series of sites ranging from oral to scribal to print. As printed words and images increased in number and extended their reach in the nineteenth century, they commingled with other forms that remained crucial in the construction of individual identities and discursive communities engaged in social and moral reform.